Leveraging Brand Innovativeness to Build Trend-Driven Value and Customer Satisfaction - Muhammad Hilmi Labibunnajah; Abdul Ghofur; Ninda Fatmawati (Journal of Digital Marketing and Halal Industry, 2026)
This study addresses inconsistencies in prior research regarding the effects of fashion consciousness and brand innovativeness on customer satisfaction, particularly due to the lack of a clear underlying mechanism. The rapid proliferation of social media has intensified trend sensitivity among fashion consumers, making trend-based value increasingly important. Drawing on Consumer Value Theory and the expectation-confirmation model, this study examines perceived value on trendiness (PVT) as a mediating mechanism linking brand innovativeness (BI), fashion consciousness (FC), and customer satisfaction (CS) in the Indonesian sneaker market. Using an explanatory research design to examine causal relationships, data were collected from 150 respondents through purposive sampling and analyzed using covariance-based structural equation modeling (CB-SEM) with AMOS. The results show that brand innovativeness has a significant positive effect on PVT (β = 0.613, p < 0.001), and PVT significantly influences customer satisfaction (β = 0.575, p < 0.001). However, fashion consciousness does not significantly affect PVT (β = 0.123, p = 0.239). Mediation analysis indicates that PVT significantly mediates the relationship between BI and customer satisfaction (Sobel = 3.394, p < 0.001), but not the relationship between FC and customer satisfaction. This study contributes to the literature by extending perceived value theory through the introduction of trendiness as a value dimension that mediates the relationship between brand innovativeness and customer satisfaction.